2011
DOI: 10.1186/1743-7075-8-75
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for carbohydrate restriction in the treatment and prevention of cancer?

Abstract: Over the last years, evidence has accumulated suggesting that by systematically reducing the amount of dietary carbohydrates (CHOs) one could suppress, or at least delay, the emergence of cancer, and that proliferation of already existing tumor cells could be slowed down. This hypothesis is supported by the association between modern chronic diseases like the metabolic syndrome and the risk of developing or dying from cancer. CHOs or glucose, to which more complex carbohydrates are ultimately digested, can hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
1
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 143 publications
3
130
1
18
Order By: Relevance
“…The intake of Carbohydrates and protein among the participants in the present study was more than RDA, while the intake of fiber was lower than the RDA, the findings was not in line with study demonstrated the decreased in carbohydrate intake with increased chemotherapy dosage (Klement, & Kämmerer, 2011). On the other hand, another study found that increased in protein intake associated with increased chemotherapy doses (Altgelt & Mccullochm, 2012).…”
Section: Issn (Onlinecontrasting
confidence: 53%
“…The intake of Carbohydrates and protein among the participants in the present study was more than RDA, while the intake of fiber was lower than the RDA, the findings was not in line with study demonstrated the decreased in carbohydrate intake with increased chemotherapy dosage (Klement, & Kämmerer, 2011). On the other hand, another study found that increased in protein intake associated with increased chemotherapy doses (Altgelt & Mccullochm, 2012).…”
Section: Issn (Onlinecontrasting
confidence: 53%
“…However, the autoimmune nature of T1D may complicate the interpretation of this result, because the immune system plays a pivotal role in cancer cell surveillance (Allavena & Mantovani 2012, Haabeth et al 2012. In vitro studies also showed that adding insulin to the medium containing high glucose promoted the sequential activation of PI3K, AKT, and mTOR leading to the increased anabolic activity in cancer cells and subsequent 20-40% enhanced proliferation rates (Klement & Kammerer 2011, Ward & Thompson 2012. However, in these experiments, the effects of hyperinsulinemia and hyperglycemia could not be disentangled as both were present and the tissue culture medium contained high levels of glucose.…”
Section: Hyperglycemia Vs Hyperinsulinemia As a Cancer-diabetes Linkmentioning
confidence: 96%
“…Over the last century, cancer patients have been reported to exhibit signs of early glucose intolerance and insulin insensitivity, most likely as a result of an acute phase inflammatory response induced by the tumor (Marat et al 1999, Klement & Kammerer 2011. On the other hand, enhanced glucose uptake is a well-known metabolic hallmark of cancer cells.…”
Section: Hyperglycemia May Feed Cancer Cells: the Sweet Kiss Of Deathmentioning
confidence: 99%
“…These diets have not only led to weight loss without direct calorie restriction they have resulted in improvement in the risk factors associated with CVD when animal and other fats are used (Foster et al 2003;Volek et al 2003;Herron et al 2004;Sharman and Volek 2004;Volek and Sharman 2004;Yancy et al 2004Yancy et al , 2010Brinkworth et al 2009;Sacks et al 2009). Moreover, trials of ketogenic diets in the treatment of final stage cancer patients and in experimental systems (Tisdale et al 1987;Breitkreutz et al 2005;Zuccoli et al 2010;Ho et al 2011;Klement and Kaemmerer 2011;Schmidt et al 2011;Chang et al 2013) have occurred, with some interesting results of reduction in tumour size, reduction of cachexia, or delay of initiation of cancer. Ketogenic diets continue to be used to treat some classes of epilepsy (Freeman et al 1998;Kossoff et al 2006;Neal et al 2008), and have been suggested for other mental disorders or dementias including Alzheimer's disease and Parkinson's disease (VanItallie and Nufert 2003;Kim et al 2007;Kossoff and Hartman 2012).…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%